"My taste has changed" ......is it because of the dental procedure I underwent???? A Case Report and Review of Literature - Mehrotra, Y (Bangladesh Journal of Dental Research & Education, 2014)
DOI: http://dx.doi.org/10.3329/bjdre.v4i1.18017 Bangladesh Journal of Dental Research & Education Vol.4(1) 2014: 42-48